Ash cenosphere fragmentation during pulverised pyrite combustion: Importance of cooling - Wu, Hongwei; Li, Y. (Combustion Institute, 2018)
This paper as the first time in the field reports the direct experimental evidence for demonstrating the important role of cooling in ash cenosphere fragmentation using a simple but unique combustion system. The combustion system used pulverised pyrite (38-45 µm) for combustion in drop-tube furnace under designed conditions (gas temperature: 1000 °C; residence time: 1.2 s), which produced dominantly ash cenosphere particles or fragments. The combustion products were quenched under various cooling conditions (represented by nominal cooling rates of 6400-11,800 °C/s) for sampling. The results show that increasing cooling rate from 6400 to 11,800 °C/s substantially intensifies ash cenosphere fragmentation. Such enhanced ash cenosphere fragmentation leads to a significant shift in the particle size distribution of ash collected in the cyclone (>10 µm) to much smaller sizes. It also produces considerably more particulate matter (PM) with aerodynamic sizes less than 10 µm (i.e., PM10) that consists of dominantly PM with aerodynamic sizes between 1 and 10 µm (i.e., PM1-10) and some PM with aerodynamic sizes less than 1 µm (i.e., PM1). It is further noted that the PM1is mainly PM with aerodynamic sizes between 0.1 and 1 µm (i.e., PM0.1-1) and to a considerably lesser extent PM with aerodynamic sizes less than 0.1 µm (i.e., PM0.1). Chemical analyses further show that both ash and PM samples contain only Fe2O3, indicating that complete consumption of sulphur and full oxidation of iron have been achieved during pulverised pyrite combustion under the conditions.